hw9-sol.pdf

# hw9-sol.pdf - UC Berkeley Department of Electrical...

• Homework Help
• 6
• 100% (4) 4 out of 4 people found this document helpful

This preview shows pages 1–3. Sign up to view the full content.

UC Berkeley Department of Electrical Engineering and Computer Sciences EECS 126: Probability and Random Processes Problem Set 9 Spring 2018 Self-Graded Scores Due: Monday, March 26, 2018 Submit your self-graded scores via the Google form: . Make sure you use your SORTABLE NAME on CalCentral. 1 . Basketball II Team A and Team B are playing an untimed basketball game in which the two teams score points according to independent Poisson processes. Team A scores points according to a Poisson process with rate λ A and Team B scores points according to a Poisson process with rate λ B . The game is over when one of the teams has scored k more points than the other team. Find the probability that Team A wins. Solution: We consider the merged process with rate λ A + λ B and notice that each point is a point for A with probability p = λ A / ( λ A + λ B ) and a point for B with probability 1 - p = λ B / ( λ A + λ B ). Now, we consider the following Markov chain. Let the state of the chain be the number of additional points Team B needs to score to win. Thus, we have the transition probabilities: P 0 , 0 = 1 P i,i +1 = p, where 0 < i < 2 k P i,i - 1 = 1 - p, where 0 < i < 2 k P 2 k, 2 k = 1 0 · · · i · · · 2 k 1 1 1 - p p p p 1 - p 1 2 We are looking for the probability that a random walk, starting at state k hits state 2 k (as this indicates that Team A won). Now, let P i be the probability that starting at state i , Team A will win (equivalently, the probability of ending in state 2 k when starting at state i ). We let ρ = (1 - p ) /p . We also claim that P i - P i - 1 = ρ i - 1 P 1 for i > 1. We shall show this by induction. Consider the base case P 2 - P 1 . Note that P 1 = pP 2 + (1 - p ) P 0 = pP 2 since P 0 = 0. 1

This preview has intentionally blurred sections. Sign up to view the full version.

We thus see that P 2 - P 1 = ρP 1 . Now, we assume for all i , 0 < i < n , that P i - P i - 1 = ρ i - 1 P 1 . We would like to show that P n - P n - 1 = ρ n - 1 P 1 . We note that P n - 1 = pP n + (1 - p ) P n - 2 . This implies that: P n = 1 p ( P n - 1 - P n - 2 + pP n - 2 ) = 1 p ( ρ n - 2 P 1 + pP n - 2 ) .
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern